An Examination of Cognitive Biases and Imagery in Perfectionism - Howell, Joel Aaron (Curtin University, 2017)
This present research explores the relationship between perfectionism and the tendency for individuals to focus their attention towards, and interpret ambiguous information as, stimuli that signals failure. The relationship between perfectionism, repetitive negative thinking, imagery and psychological distress was also explored. Perfectionism was associated with an increased likelihood to focus on failure, interpret ambiguous information in way that indicated failure, and were more likely to experience distress due to intrusive images about the future.